The son of Neptune - Riordan, Rick (The heroes of Olympus, 2011)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled.